Management of hemostatic complications in acute leukemia: guidance from the SSC of the ISTH - Wang, Tzu-Fei (J Thromb Haemost, 2020)
Patients with acute leukemia frequently develop thrombocytopenia and hemostatic complications caused by coagulopathy. Coagulopathy complicates the management of these patients and can lead to significant morbidity and mortality. This guidance document aims to review and provide guidance on the management of hemostatic complications in adult patients with acute leukemia, addressing four main issues, including platelet transfusion, disseminated intravascular coagulation, L-asparaginase-related hypofibrinogenemia, and the use of antifibrinolytic agents.